Element Birth and Death Method Application to Lamellar Crack Analysis - Jaroniek, Mieczysław; Niezgodziński, Tadeusz (Wydawnictwo Politechniki Łódzkiej ; Katedra Dynamiki Maszyn - Wydział Mechaniczny Politechniki Łódzkiej, 2015)
Load structure, the maximum permissible load is usually determined by the strength calculation (bearing data. Yield stress or strength of the material), or the parameters of fracture mechanics. The paper analyzes the calculations lamellar cracks formed in the lower crane girders steel belts. These cracks are formed in rolled sheets of non-metallic inclusions. The determination of the cracks in the existing designs are extremely difficult. It requires testing metallographic, ultrasonic or acoustic methods. Based on typical images of metallographic steel plates specified place of occurrence of cracks lamellar and sampling, and has subsequently been adopted for the calculation of numerical models of material structure and distribution of artificial joints. In order to analyze the propagation of cracks and formation of lamellar phase slots and destruction was carried out modeling studies and numerical methods cracking process.
Keywords: FEM; model of fracture; stress intensity-factor; lamellar cracks; model pęknięcia; współczynnik intensywności naprężeń; pęknięcia blaszkowe; finite element mehod; metoda elementów skończonych